Benzothienoisoindigo-based polymers for efficient polymer solar cells with an open-circuit voltage of 0.96 V. (26th June 2019) - Lu, Jie; Zhou, Huangshan; Yu, Yufu; Liu, Hailu; Peng, Lini; He, Pingxiang; Zhao, Bin
Abstract: Two conjugated polymers have been designed and synthesized by introducing benzothienoisoindigo as electron-withdrawing moieties on side chains. PBDTT-TBID based on alkylthienyl-substituted benzo[1, 2- b :4, 5- b ']dithiophene (BDT) derivative as electron-donating moieties possesses a low-lying highest occupied molecular orbital energy level of −5.38 eV, so its polymer solar cells (PSCs) shows a high open-circuit voltage ( V oc ) of 0.96 V, which is one of the highest V oc values among benzothienoisoindigo-based polymers. PBDT-TBID based on alkoxyl-substituted BDT derivative possesses better molecular coplanarity, stronger intramolecular charge transfer, stronger intermolecular π-π stacking, more suitable microphase separation with PC71 BM, more effective exciton dissociation, and higher hole mobility than PBDTT-TBID, which lead to higher short-circuit current density ( J sc = 11.81 mA cm −2 ), fill factor (FF = 0.58) and power conversion efficiency (PCE = 5.87%) values than those based on PBDTT-TBID . The PCE value is still higher than those of the reported benzothienoisoindigo-based polymers though it lags behind those of recent non-fullerene PSCs. Graphical abstract: Image 1 Highlights: Benzothienoisoindigo-based polymer achieves a V oc of 0.96 V. PBDT-TBID shows the best photovoltaic performance in benzothienoisoindigo -based polymers. The effects of the side chains on the properties of the polymers are studied.